Polymeric nanofiltration membranes for textile dye wastewater treatment: preparation, performance evaluation, transport modelling, and fouling control - a review - Laua, Woei-Jye (Elsevier BV, 2009)
This paper reviews the application of polymeric nanofiltration membranes (NF) in the specific waste stream in the textile industry, which typically generates large volumes of wastewater containing complex contaminants from its daily operation. It is necessary that as much of this waste as possible is recycled instead of being disposed of in landfill sites. Most of the conventional technologies seem unable to provide sufficient treatment for the effluents. Therefore, it is generally accepted that NF membranes offer solutions for the problem. Of these NF membranes, the thin-film composite nanofiltration (TFC-NF) membrane is the most widely used by researchers in their studies. The effects of the manufacturing conditions of TFC-NF are discussed to provide valuable information for those who are going to choose NF membranes in textile wastewater treatment. The preliminary performances of commercial NF membranes have been examined in terms of dye rejection, salt rejection, permeate flux and COD rejection. Some of the commercial membranes achieved maximum separation of dye and salts while some achieved higher flux. This is because of the large variability of the parameters of textile wastewater and the NF membranes chosen. Due to the scarcity of published papers covering the transport model that is specifically suitable for textile coloured wastewater, a brief review of transport models of NF membranes with the presence of the dyes and salts is given. Membrane fouling mechanisms and methods to control fouling are also reviewed. Future directions in NF membrane research are also discussed to further expand research and development related to textile wastewater treatment.